Enhancing Drawing Education through Innovative Approaches - Raximova Gulsanam Hazrat qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the role of innovative approaches in enriching drawing education. The study focuses on the integration of digital technologies, interactive methods, and project-based learning to improve students’ creative and technical skills. Emphasis is placed on methods that promote independent creative activity, foster problem-solving abilities, and develop visual and technical competencies in students through modern pedagogical strategies.